2019
DOI: 10.9734/ajarr/2019/v6i230149
|View full text |Cite
|
Sign up to set email alerts
|

Customer Satisfaction towards Online Shopping in Sri Lanka: Moderating Effect of Income Level

Abstract: Aim: Online shopping is the most popular feature around the world as well as in Sri Lanka. People are tending to do online shopping by using those social media and also by using online shopping websites. As well as most of the business organizations try to use online shopping to sell their product and to increase their market. The objective of this research is to assess the factors influencing customer satisfaction while doing online shopping. Further, the study tested the moderating effect of income level on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
(21 reference statements)
0
2
1
Order By: Relevance
“…These may include inefficient services such as late product delivery, poor packaging, and delayed customer service feedback. Apparently, this outcome contradicts the research done by Perera et al (2019) that stated customer service is one of the main factors in determining customer satisfaction. This result suggested that e-service quality concerns were not significant as long as the product purchase is delivered to the customer, and that would be sufficient and acceptable.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…These may include inefficient services such as late product delivery, poor packaging, and delayed customer service feedback. Apparently, this outcome contradicts the research done by Perera et al (2019) that stated customer service is one of the main factors in determining customer satisfaction. This result suggested that e-service quality concerns were not significant as long as the product purchase is delivered to the customer, and that would be sufficient and acceptable.…”
Section: Discussioncontrasting
confidence: 61%
“…Therefore, retaining a customer is inevitable because the customer means profit to them. Perera et al (2019) stated that repurchase intention depends on the quality of the product and services obtained when purchasing the product online. Irantaj and Huseynov (2018) further stated that a firm requires a competitive advantage to leverage its strength to confront future challenges in e-commerce.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…In [29], it was found that income level does not affect online shopping for necessary items, such as computer accessories, and customers of all income levels shopped mostly during discounts and special offers. In [30], it was found that income level has a significant influence on the relationship between convenience, website functionality, security, customer service, and customer satisfaction with online shopping. However, these studies did not discuss whether buyers were not the same person who is responsible for paying for the online shopping transaction, where it seems to most affect perspectives towards online shopping.…”
Section: Literature Review-hypothesis Formingmentioning
confidence: 99%
“…Online purchasing can be defined as a new trend across the world. The study by Perera and Sachithra (2019) indicated online shopping is now becoming a popular way to go for sales and purchase goods. Further, it elaborates online shopping is mixed with real-life shopping by today's shoppers, using Wi-Fi connectivity and the trend of showrooming (Perera & Sachithra 2019).…”
Section: Concept Of Online Purchasingmentioning
confidence: 99%